Integrating census data with hyper-temporal NDVI data, to prepare detailed crop intensity and crop growing period maps :Powerpoint - de Bie, C.A.J.M. (University of Twente, 2020)
This lecture presents: Problem statement by Stanley Wood; Can hyper-temporal imagery make the difference?; Example on the use of hyper-temporal imagery; The case of Ethiopia; Ethiopia Maps that do report where fields are …; MoA /ATA thus needed ‘spatial guidance’ to map their data and studies: wisely they chose AEZ’s; Example of produced crop calendars (Moist Zone).